Guidance of school quality assurance: Community services on application of school quality assurance at elementary schools - Cepi Triatna (Universitas Pendidikan Indonesia, 2014)
One of the efforts to improve educational quality is quality assurance. Problems arise in the school implementation, such as people in schools do not understand the implementation of quality assurance in managing school. Community Services on Application of Quality Assurance is predicted as a program solution of these problems. Through academicians (students and lectures) assistance on implementing school quality assurance, the school management will running well step by step. This program includes of three main program. First to identify, level of school quality through school self-evaluation using eight national education standards. Second, to help school to make strategic plan based on school self evaluation. Third, to help the school to develop school website. Hopefully school will be getting used to manage the school with quality of culture and understanding of quality assurance. Communities targeted in this program is elementary school at Sukasari Sub-District, Bandung, West Java.